Contextualizing reliability and validity in qualitative research: toward more rigorous and trustworthy qualitative social science in leisure research. (7th August 2020) - Rose, Jeff; Johnson, Corey W.
Abstract: Issues of trustworthiness in qualitative leisure research, often demonstrated through particular techniques of reliability and/or validity, is often either nonexistent, unsubstantial, or unexplained. Rather than prescribing what reliability and/or validity should look like, researchers should attend to the overall trustworthiness of qualitative research by more directly addressing issues associated with reliability and/or validity, as aligned with larger issues of ontological, epistemological, and paradigmatic affiliation. In reviewing contemporary qualitative research methodologies, we present a variety of reliability and validity techniques that might lead to increased trustworthiness in analysis and representation of findings. Qualitative leisure scholars are encouraged to align paradigmatic assumptions, theoretical orientations, methodological practices, analytical techniques, and representational practices to engage trustworthiness techniques that can be assessed for quality and credibility. This conceptualization offers a useful pedagogical model and supports common language of qualitative preferred practices, while providing space and openness for growth, development, improvisation, and critique.